Variability in adherence to rhGH treatment: Socioeconomic causes and effect on children's growth. (February 2016) - De Pedro, Silvina; Murillo, Marta; Salinas, Isabel; Granada, Maria-Luisa; Martinez, María; Puig-Domingo, Manel; Andreu, Angels; Bel, Joan
Abstract: Background: In children with growth disorders, mean final height is associated to poor adherence to Growth Hormone therapy. The primary goal of this study is to identify patients who do not adhere to GH therapy and determine the influence of adherence in response to the treatment. The role of serum IGF-I and influence of socio-economic factors on the therapeutic adherence will also be evaluated. Methods: 158 children under treatment with rhGH were included in the study. Age, gender, etiology, Tanner stage, duration of treatment, growth rate, IGF-I serum values, daily dose, and annual rhGH dose data were collected. Adherence to therapy was defined as moderate-to-poor when the patient had taken less than 92% of the prescribed medication. A subgroup of 106 patients completed a questionnaire to assess social and environmental effects. Results: Moderate-to-poor adherence to rhGH treatment was determined in 33.5% of study patients. A decrease in adherence was associated to treatment duration ( p = 0.001). A significant correlation was determined between adherence and height velocity ( p = 0.002) and IGF-I ( p < 0.0001) levels. Adherence rates were associated to the mother's educational level ( p = 0.007). Conclusion: Poor adherence to GH therapy was observed in one-third of study patients, resulting in suboptimal growth. IGF-I levels can be helpful to identify patients with poor adherence to GH medication. Physicians should pay special attention to certain characteristics of the patient and their environment, and encourage desirable therapeutic compliance. Highlights: A major cause of failure of GH therapy can be patient noncompliance. The prevalence of non-adherence to pediatric GH therapy varies from 36% to 49%. There is conflicting evidence about an association between adherence and socioeconomic status. IGF-I levels could be helpful to identify patients with lower adherence.